2010
DOI: 10.1007/s11219-010-9104-9
|View full text |Cite
|
Sign up to set email alerts
|

Resumption strategies for interrupted programming tasks

Abstract: Interrupted and blocked tasks are a daily reality for professional programmers. Unfortunately, the strategies programmers use to recover lost knowledge and rebuild context when resuming work have not yet been well studied. In this paper, we describe an exploratory analysis performed on 10,000 recorded sessions of 86 programmers and a survey of 414 programmers to understand the various strategies and coping mechanisms developers use to manage interrupted programming tasks. Based on the analysis, we propose a fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 48 publications
3
69
0
Order By: Relevance
“…For example, by observing software developers and other information workers at work, Mark et al found that 57% of all tasks are interrupted and are thus often fragmented into small work sessions [29] and Chong and Siino found that most interruptions-many of them were also self-initiated-lasted around 2 to 3 minutes [26]. While many of these interruptions are necessary, they can lead to a higher error rate, slow task resumption and an overall lower work performance [9], [30], [31], [32]. Parnin and Rugaber found, for instance, that only one out of ten interrupted programming tasks is being continued within a minute after the interruption [9].…”
Section: Work Fragmentationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, by observing software developers and other information workers at work, Mark et al found that 57% of all tasks are interrupted and are thus often fragmented into small work sessions [29] and Chong and Siino found that most interruptions-many of them were also self-initiated-lasted around 2 to 3 minutes [26]. While many of these interruptions are necessary, they can lead to a higher error rate, slow task resumption and an overall lower work performance [9], [30], [31], [32]. Parnin and Rugaber found, for instance, that only one out of ten interrupted programming tasks is being continued within a minute after the interruption [9].…”
Section: Work Fragmentationmentioning
confidence: 99%
“…While many of these interruptions are necessary, they can lead to a higher error rate, slow task resumption and an overall lower work performance [9], [30], [31], [32]. Parnin and Rugaber found, for instance, that only one out of ten interrupted programming tasks is being continued within a minute after the interruption [9].…”
Section: Work Fragmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…After an interruption, people have to scan and evaluate all new information that they have encountered; several short interruptions have a greater effect than one long interruption . Parnin and Rugaber (2011) analyzed 10 000 programming sessions and found that developers returning to a task after an interruption, such as a meeting, needed 15 minutes or more to collect their thoughts and make the first edit for most tasks (57%).…”
Section: Meetings In Generalmentioning
confidence: 99%
“…Previous work has shown that interruptions are one of the biggest impediments to productive work, distracting developers from their main task and resuming it takes on average about 15 minutes [13,18]. My goal is to reduce interruptions at inopportune, costly moments by provisioning actionable insights to an individual developer that increase the awareness about co-workers' current focus at work.…”
Section: For Co-workersmentioning
confidence: 99%